Uso da tecnologia da informação na gestão da cadeia de suprimentos a visão dos fornecedores de São Luís do Maranhão - Morais, Káty Maria Nogueira (2010)
The use of Information Technology in supply chain management has been a source of competitive advantage, mainly in times of increasing competitiveness. However, there have not been many publications about this use in the market of Brazil’s Northeast. Considering this, the relevance of this research is highlighted, since it aims to analyze how Information Technology has been used to support supply chain management in the state of Maranhão. The characteristics of the local market, the current suppliers and the potential of the state are shown. Based on the theoretical background, the research instrument was developed, consisting of a survey validated as the methodology presented by the literature suggested. The results of the field work research contribute to the implementation of development strategies for IT used by Maranhense suppliers and, consequently, for local development. This data allows the confirmation, in general terms, of the incipient use of specific technological instruments in the management of supply chains among local suppliers.